Comparison of horizontal axis wind turbine (HAWT) and vertical axis wind turbine (VAWT) - Khudri Johari, Muhd; Azim A Jalil, Muhammad; Faizal Mohd Shariff, Mohammad (International Journal of Engineering and Technology, 2018)
As the demand for green technology is rising rapidly worldwide, it is important that Malaysian researchers take advantage of Malaysiaâ€™s windy climates and areas to initiate more power generation projects using wind. The main objectives of this study are to build a functional wind turbine and to compare the performance of two types of design for wind turbine under different speeds and behaviours of the wind. A three-blade horizontal axis wind turbine (HAWT) and a Darrieus-type vertical axis wind turbine (VAWT) have been designed with CATIA software and constructed using a 3D-printing method. Both wind turbines have undergone series of tests before the voltage and current output from the wind turbines are collected. The result of the test is used to compare the performance of both wind turbines that will imply which design has the best efficiency and performance for Malaysiaâ€™s tropical climate. While HAWT can generate higher voltage (up to 8.99 V at one point), it decreases back to 0 V when the wind angle changes. VAWT, however, can generate lower voltage (1.4 V) but changes in the wind angle does not affect its voltage output at all. The analysis has proven that VAWT is significantly more efficient to be built and utilized for Malaysiaâ€™s tropical and windy climates. This is also an initiative project to gauge the possibility of building wind turbines, which could be built on the extensive and windy areas surrounding Malaysian airports.Â Â